Fracture toughness and impact strength of hollow epoxy particles-toughened polyester composite - Low, L.F.; Abu Bakar, A. (Universiti Kebangsaan Malaysia, 2013)
Hollow epoxy particles (HEP) serving as reinforcing fillers were prepared using the water-based emulsion method in this study. HEP was incorporated into the polyester matrix at various loading, ranging from 0 wt% to 9 wt%, to toughen the brittle polyester thermoset. The polyester composites were prepared using the casting technique. The fracture toughness and impact strength of the polyester composites increased with increasing the HEP loading up to 5 wt%, after which there was a drop. The improvement in fracture toughness and impact strength is attributed to the good polymer-filler interaction. This finding was further supported by the scanning electron micrograph, in which it was shown that the polyester resin was interlocked into the pore regions of the HEP filler. The reduction in fracture toughness and impact strength of the polyester composite were believed to be attributed to the filler agglomeration. This filler-filler interaction would create stress concentration areas and eventually weakened the interfacial adhesion between the polymer matrix and the filler particles. Hence, lower fracture toughness and impact strength of the highly HEP-filled polyester composites (above 5 wt%) were detected.